Method and system for filling space

JP2024111720A5Active Publication Date: 2025-01-30JAPAN ORG FOR METALS & ENERGY SECURITY +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023016392
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-02-06
Publication Date
2025-01-30
Estimated Expiration
2043-02-06

AI Technical Summary

Technical Problem

Existing methods struggle to efficiently fill partially narrowed or complicated spaces, such as those found in closed coal mines, with a filling material that has high fluidity and controlled solidification properties to ensure complete coverage and minimize premature solidification near the injection port.

Method used

A method and system using a slurry composition containing hydraulic materials, alkaline stimulants, dispersants, and curing inhibitors, which is injected under pressure and reacts with carbon dioxide to solidify and fill spaces, allowing for controlled solidification and efficient filling of complex shapes.

Benefits of technology

The method enables efficient filling and solidification of spaces with appropriate fluidity and solidification properties, effectively fixing carbon dioxide and minimizing premature solidification, thereby enhancing the efficiency and strength of space burial while contributing to global warming mitigation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a method and system for filling a space by injecting a slurry of a specific composition into the space and reacting it with carbon dioxide.SOLUTION: Disclosed is a method of filling a space including: preparing a composition containing a hydraulic material and at least one selected from the group consisting of an alkali stimulator, a dispersant, and a hardening inhibitor; and injecting a slurry containing the composition into the space and reacting the slurry with carbon dioxide injected into the space together with the slurry or with carbon dioxide that has been injected into the space separately from the slurry. The space may include at least one selected from the group consisting of a pore in a stratum, an underground tunnel, and a coal mining site. The hydraulic material may include an aluminosilicate material. The aluminosilicate material may include a blast furnace slag. The alkali stimulant may include sodium hydroxide.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method and system for filling a void. More specifically, the present invention relates to a method and system for filling a void by injecting a slurry of a specific composition into the void and reacting it with carbon dioxide. [Background technology]

[0002] Greenhouse gases such as carbon dioxide are believed to be the cause of global warming, and efforts to reduce their emissions are being made in various countries. In response, developed countries, including Japan, are promoting the development of technologies to fix carbon dioxide, a greenhouse gas, as a component of mineral structures (called "mineralization of carbon dioxide" or "mineral carbonation"). Research on minerals used for mineralization of carbon dioxide has expanded from natural rocks and silicate minerals such as basalt, olivine, serpentine, and wollastonite to various types of industrial by-products or waste materials.

[0003] Examples of industrial by-products or waste materials that are minerals that can be used for the mineralization of carbon dioxide include waste cement, waste concrete, and blast furnace slag, which is generated from components other than iron contained in iron ore used in the steel industry and contains a large amount of CaO. For example, Patent Document 1 discloses a carbon dioxide fixation method in which carbon dioxide is supplied to an aqueous solution of a mixture of granulated blast furnace slag, which is a specific type of blast furnace slag, and an alkali, and the supplied carbon dioxide reacts with calcium dissolved from the slag to produce CaCO3 (calcium carbonate). Patent Document 2 discloses a carbon dioxide fixation method that includes adding NaOH to a mixture of a predetermined ratio of pulverized blast furnace slag and water to decompose the blast furnace slag, and then hydrothermally reacting the blast furnace slag with carbon dioxide. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-214262 A [Patent Document 2] JP 2013-095662 A Summary of the Invention [Problem to be solved by the invention]

[0005] For example, in closed coal mines, the space to be filled is often partially narrowed or complicated due to deformation or submergence of pores or underground cavities in the strata, etc. Therefore, in order to fill every corner of such partially narrowed or complicated spaces with a filling material, it is preferable that the fluidity of the filling material is sufficiently high, and that the filling material has a solidification performance that suppresses solidification near the injection port in the space to be filled by controlling and delaying the solidification time, while at the same time proceeding to solidification when the filling material has spread throughout the entire space.

[0006] The present invention aims to provide a method and system that enables a solidification material having suitable fluidity and solidification properties to be efficiently filled into a space, reacted with carbon dioxide, a greenhouse gas, to solidify, and fill the space. [Means for solving the problem]

[0007] As a result of extensive research, the inventors discovered that by using a composition containing specific components as a solidification substance, making this into a slurry, injecting it under pressure, allowing it to react with carbon dioxide and burying it in a space, it is possible to efficiently fill and solidify the space, and thus completed the present invention.

[0008] That is, one aspect of the present invention for achieving the above object is as follows. A method for filling a space, comprising the steps of: Preparing a composition containing a hydraulic material and at least one selected from the group consisting of an alkaline irritant, a dispersant, and a hardening inhibitor; A method comprising injecting a slurry containing the composition into a space and filling the space by reacting the composition with carbon dioxide injected into the space together with the slurry or with carbon dioxide injected into the space separately from the slurry.

[0009] Another aspect of the present invention for achieving the above object is as follows. A space embedding system, comprising: a slurry preparation unit that prepares a slurry using a composition containing a hydraulic material and at least one selected from the group consisting of an alkaline stimulant, a dispersant, and a hardening inhibitor; a slurry injection unit that injects the slurry or the slurry and carbon dioxide into a space; and a carbon dioxide injection unit that separately injects carbon dioxide into the space when the slurry injection unit is a slurry injection unit that injects the slurry into the space without carbon dioxide. Effect of the Invention

[0010] According to the method for filling a space (or the system for filling a space) of the present invention, a slurry of a composition, which is a solidifying substance having suitable fluidity and solidification properties, is injected into the space and reacted with carbon dioxide, a greenhouse gas, thereby making it possible to efficiently fill and solidify spaces of various shapes, thereby filling the space. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic diagram of an embodiment in which the space burying method (burying system) according to the present invention is applied to an abandoned underground coal mine site in an underground coal mine. [Diagram 2] FIG. 2 is a photograph showing the appearance of a composition slurry when it is removed from a formwork after being in contact with carbon dioxide for 24 hours in an embodiment of the space filling method according to the present invention, in which the composition slurry does not contain an alkaline irritant but does contain a chelating agent. [Diagram 3]FIG. 3 is a drawing showing an external photograph (left side (A)) of a composition slurry containing an alkaline irritant and no hardening inhibitor when it is removed from a formwork after being in contact with carbon dioxide for 24 hours in an embodiment of the space filling method according to the present invention, and an external photograph (right side (B)) of a composition slurry containing an alkaline irritant and no hardening inhibitor when it is removed from a formwork after being in contact with carbon dioxide for 24 hours. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the embodiment of the present invention will be described. The present invention is not limited to the description of the following embodiment. Since the space filling system according to the present invention is essentially a system for realizing the space filling method according to the present invention, the embodiment of the filling method will be mainly described below.

[0013] How to fill the space The method for filling a space according to the present invention includes preparing a composition containing a hydraulic material and at least one selected from the group consisting of an alkaline irritant, a dispersant and a hardening inhibitor. In a preferred embodiment, the method includes preparing a composition containing a hydraulic material and an alkaline irritant, and optionally containing at least one selected from the group consisting of a dispersant and a set inhibitor. In yet another embodiment, the method includes preparing a composition containing a hydraulic material and an alkaline irritant, and optionally containing at least one selected from the group consisting of a dispersant, a set inhibitor, and a chelating agent (metal release agent). In yet another embodiment, the method includes preparing a composition containing a hydraulic material and, optionally, at least one selected from the group consisting of an alkaline irritant, a dispersant, a set inhibitor, and a chelating agent (metal release agent). It should be noted that the components of the composition used in this method are not limited to those described herein, and may contain other optional components as long as they do not impair the desired properties.

[0014] hydraulic material In one embodiment, the hydraulic material, which is one component of the composition used in the method for filling a space according to the present invention, is not particularly limited as long as it is a substance that can react with water at a predetermined pH to liberate and release metal ions and fix carbon dioxide as a mineral (mineralize) by hardening together with the metal ions, and examples of the hydraulic material include steel slag such as blast furnace slag and steelmaking slag, fly ash, copper slag, Portland cement, mixed cement, alumina cement, blast furnace cement, and other cements. Hydraulic materials are also called "binders" from the perspective of their functionality. Among these hydraulic materials, from the viewpoint of stable mineralization and fixation of carbon dioxide, materials containing aluminosilicate such as blast furnace slag and fly ash, or mixtures thereof, are preferred. Among the aluminosilicate-containing materials, blast furnace slag is more preferred. These hydraulic materials may be used alone or in admixture of two or more kinds.

[0015] Blast furnace slag is a material that is recovered from a blast furnace, which is a smelting furnace that reduces and melts iron ore with coke to produce pig iron, by melting and melting the iron ore together with other components contained in the iron ore, mainly the auxiliary material limestone and ash in the coke. Blast furnace slag includes slowly cooled slag, which is obtained by slowly cooling the molten material, and granulated slag, which is obtained by rapidly cooling the molten material. Slowly cooled slag is crystalline and rock-like, while granulated slag is glassy and finely granulated. Blast furnace slag is mainly composed of CaO (calcium oxide: quicklime), SiO2 (silica), and Al2O3 (alumina), and the CaO content is usually about 40 to 45 mass%, and the mass ratio of SiO2 can be about 30 to 35 mass%. Fine powder of blast furnace slag forms a stable hydrate in the presence of an alkaline aqueous solution, providing the function of densifying the hardened body structure.

[0016] In a preferred embodiment, the blast furnace slag may be pulverized prior to mixing with water to form a slurry. For example, it is preferred to pulverize the blast furnace slag to a size between 100 mesh and 600 mesh, and more preferably to a size between 200 mesh and 600 mesh. By using pulverized blast furnace slag in this manner, the efficiency of the reaction of the slurry with carbon dioxide (i.e., the carbonation reaction) can be increased.

[0017] Fly ash is a molten fine coal ash particle generated by the combustion of coal in a boiler. After floating in the high-temperature combustion gas, the fly ash becomes spherical fine particles as the temperature at the boiler outlet drops. Fly ash is usually collected by an electrostatic precipitator at the boiler outlet. The main components of fly ash (usually about 70-80 mass%) are SiO2 (silica) and Al2O3 (alumina), and the main constituent phases are glass phase (amorphous Al-Si), crystalline silica (quartz), and crystalline aluminosilicate (3Al2O3·2SiO2: mullite). Fly ash may contain ferric oxide (Fe2O3), calcium oxide (CaO), magnesium oxide (MgO), magnetite (Fe3O4), etc., in addition to SiO2 and Al2O3. Of the above constituent phases, the glass phase has pozzolanic reactivity with alkaline substances such as calcium hydroxide. That is, the glass phase of fly ash, in the presence of calcium hydroxide produced by, for example, cement hydration, slowly reacts with it to produce calcium silicate hydrate and calcium aluminate hydrate, which enhances the durability and watertightness of the hardened material (immobilized carbon dioxide and mineralized material). Fly ash may have a particle size of about 0.1 to 300 μm. Fly ash may contain trace amounts of heavy metals such as selenium, fluorine, boron, and arsenic.

[0018] Alkaline stimulant In one embodiment, the alkaline stimulant that can be selected as one component of the composition used in the method for filling a space according to the present invention is not particularly limited as long as it can impart alkaline stimulation to the hydraulic material and promote its hydration and hardening. The alkaline stimulant also has the function of promoting the pozzolanic reaction of the hydraulic material. Examples of such alkaline stimulants include, but are not limited to, calcium hydroxide (slaked lime: Ca(OH)2), sodium hydroxide (NaOH), potassium hydroxide (KOH), sodium carbonate (Na2CO3), potassium carbonate (K2CO3), sodium sulfate (Na2SO4), calcium nitrite (Ca(NO2)2), aluminum sulfate (Al2(SO4)3), various gypsums (anhydrous gypsum: calcium sulfate (CaSO4), its dihydrate and hemihydrate), various cements, lime dust, sodium silicate (water glass: Na2O·SiO2), etc. Among these alkaline stimulants, calcium hydroxide, sodium hydroxide, and sodium silicate are preferred from the viewpoint of functionality in promoting hydration and hardening of hydraulic materials. Sodium hydroxide is more preferred from the viewpoint of availability and cost. These alkaline irritants may be used alone or in combination.

[0019] Sodium silicate (water glass: Na2O·SiO2) can cause gelation and plasticization reactions when coexisting with hydraulic materials (e.g. blast furnace slag) during the hardening reaction with carbon dioxide, and subsequently promote the hardening of the hydraulic material, resulting in an increase in early strength and even an increase in the strength of the final hardened product. The nature of the hydration reaction between sodium silicate (water glass) and hydraulic materials can be determined by the molar ratio SiO2 / Na2O of the SiO2 and Na2O components in sodium silicate. The mass ratios of various components, including SiO2 and Na2O, in sodium silicate are standardized by JIS K1408-1966, with "No. 1" being 35-38% by mass of SiO2:17-19% by mass of Na2O, "No. 2" being 34-36% by mass of SiO2:14-15% by mass of Na2O, "No. 3" being 28-30% by mass of SiO2:9-10% by mass of Na2O, "sodium metasilicate type 1" being 27.5-29% by mass of SiO2:8.5-30% by mass of Na2O2, and "sodium metasilicate type 2" being 19-22% by mass of SiO2:20-22% by mass of Na2O.

[0020] The amount of the alkaline irritant in the above composition (if used) is not particularly limited, but from the viewpoint of sufficiently promoting the hydration and hardening of the hydraulic material and from the viewpoint of the balance between these desired effects and efficiency and economy, the amount of the alkaline irritant is, for example, 0.05 parts by mass or more and 5 parts by mass or less, preferably 0.05 parts by mass or more and 4 parts by mass or less, 0.05 parts by mass or more and 3 parts by mass or less, 0.05 parts by mass or more and 2 parts by mass or less, 0.05 parts by mass or more and 1 part by mass or less, 0.05 parts by mass or more and ... 0.8 parts by mass or less, 0.07 parts by mass or more and 5 parts by mass or less, 0.07 parts by mass or more and 4 parts by mass or less, 0.07 parts by mass or more and 3 parts by mass or less, 0.07 parts by mass or more and 2 parts by mass or less, 0.07 parts by mass or more and 1 part by mass or less, 0.07 parts by mass or more and 0.8 parts by mass parts by weight or less, 0.1 parts by weight or more and 5 parts by weight or less, 0.1 parts by weight or more and 3 parts by weight or less, 0.1 parts by weight or more and 2 parts by weight or less, 0.1 parts by weight or more and 1 part by weight or less, or 0.1 parts by weight and 0.8 parts by weight or less.

[0021] Other optional ingredients Dispersants In one embodiment of the space filling method according to the present invention, the dispersant that can be selected as one component of the composition is not particularly limited as long as it has the function of dispersing the inorganic hydraulic material well in the slurry. The well-dispersed state in the slurry here refers to a state in which hydraulic material particles having an average particle size of, for example, about 500 nm to 500 μm are suspended or floated in the aqueous medium without settling. By maintaining the well-dispersed state of the hydraulic material in the slurry, uniform fluidity of the slurry can be easily obtained.

[0022] The dispersant that can be used is not particularly limited, but examples thereof include polymer-type dispersants, surfactant-type dispersants, and inorganic dispersants. Examples of polymer dispersants include anionic polymer dispersants such as sulfonic acid polymers having sulfonic acid groups in the molecule, polycarboxylic acid polymers having carboxyl groups in the molecule, particularly polycarboxylic acid ether polymers having carboxyl groups and polyoxyalkylene chains in the molecule, and phosphoric acid polymers having phosphoric acid groups in the molecule; cationic polymer dispersants such as polyalkylene polyamine polymers; and nonionic polymer dispersants such as polyethylene glycol and polyether polymers.

[0023] The sulfonic acid polymer may be any compound having a sulfonic acid group or a sulfonic acid salt group in the molecule. The compound having a sulfonic acid group or a sulfonic acid salt group is preferably one having an aromatic ring in the molecule. Examples of the sulfonic acid polymers include polyalkylarylsulfonate-based polymers such as naphthalenesulfonic acid formaldehyde condensates, methylnaphthalenesulfonic acid formaldehyde condensates, and anthracenesulfonic acid formaldehyde condensates; melamine formalin resin sulfonate-based polymers such as melamine sulfonic acid formaldehyde condensates; aromatic aminosulfonate-based polymers such as aminoarylsulfonic acid-phenol-formaldehyde condensates; ligninsulfonate-based water reducers such as ligninsulfonates and modified ligninsulfonates; and polystyrenesulfonate-based polymers.

[0024] The polycarboxylic acid polymer is preferably a polymer obtained by polymerizing an unsaturated carboxylic acid monomer. When the composition does not contain an alkaline irritant, among the polycarboxylic acid polymers, a polycarboxylic acid ether polymer obtained by copolymerizing a monomer component containing an unsaturated carboxylic acid monomer and a (poly)alkylene glycol monomer is preferable. The unsaturated carboxylic acid monomer is not particularly limited as long as it has a carboxyl group and an ethylenically unsaturated hydrocarbon group, and includes unsaturated monocarboxylic acid monomers and unsaturated dicarboxylic acid monomers. Specific examples of the unsaturated monocarboxylic acid monomer include (meth)acrylic acid, crotonic acid, and the like, and their monovalent metal salts, divalent metal salts, ammonium salts, and organic ammonium salts; half esters of unsaturated dicarboxylic acid monomers and alcohols having 1 to 22 carbon atoms or glycols having 2 to 4 carbon atoms; and half amides of unsaturated dicarboxylic acid monomers and amines having 1 to 22 carbon atoms. Examples of the alcohol having 1 to 22 carbon atoms include methanol, ethanol, propanol, butanol, hexanol, and octanol. Examples of the glycol having 2 to 4 carbon atoms include ethylene glycol, propylene glycol, and diethylene glycol. Examples of the amine having 1 to 22 carbon atoms include methylamine, ethylamine, propylamine, butylamine, dimethylamine, diethylamine, dipropylamine, dibutylamine, octylamine, and dodecylamine. Specific examples of the unsaturated dicarboxylic acid monomer include maleic acid, itaconic acid, mesaconic acid, citraconic acid, fumaric acid, etc., and their monovalent metal salts, divalent metal salts, ammonium salts, organic ammonium salts, etc., and their anhydrides. As the unsaturated carboxylic acid monomer, (meth)acrylic acid (salt), maleic acid (salt), or maleic anhydride is preferable. The (poly)alkylene glycol monomer is not particularly limited as long as it has a (poly)alkylene glycol group and an ethylenically unsaturated hydrocarbon group. The (poly)alkylene glycol group is preferably an oxyalkylene group having 2 to 18 carbon atoms or a polyoxyalkylene group which is an adduct of one or more of the above oxyalkylene groups and has an average molar addition number of more than 1. The above oxyalkylene group preferably has 2 to 12 carbon atoms, more preferably 2 to 8 carbon atoms, and even more preferably 2 to 4 carbon atoms. The oxyalkylene group is an alkylene oxide adduct, and examples of such alkylene oxides include alkylene oxides having 2 to 8 carbon atoms such as ethylene oxide, propylene oxide, butylene oxide, and styrene oxide. More preferably, it is an alkylene oxide having 2 to 4 carbon atoms such as ethylene oxide, propylene oxide, and butylene oxide, and even more preferably, it is ethylene oxide or propylene oxide. When the polyalkylene glycol is an adduct of any two or more kinds of alkylene oxides selected from ethylene oxide, propylene oxide, butylene oxide, styrene oxide, etc., it may be in any form of random addition, block addition, alternating addition, etc. The average number of moles of oxyalkylene groups added to form the (poly)alkylene glycol group is preferably 1 to 300, more preferably 2 to 200, and further preferably 2 to 150. The ethylenically unsaturated hydrocarbon group is not particularly limited, but an alkenyl group having 2 to 8 carbon atoms, a (meth)acryloyl group, or the like is preferred.

[0025] As the (poly)alkylene glycol monomer, a compound represented by the following formula (1) is preferred. [ka] (In the formula, R 1 , R 2 and R 3 R may be the same or different and represents a hydrogen atom or a methyl group. 4 represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms. (R 5O) are the same or different and represent an oxyalkylene group having 2 to 18 carbon atoms. n represents the average number of moles of oxyalkylene groups added and is a number from 1 to 300. x represents a number from 0 to 4. y represents 0 or 1. In the above formula (1), preferably R 1 , R 2 is a hydrogen atom, and R 3 is a hydrogen atom or a methyl group. More preferably, R 1 , R 2 is a hydrogen atom, and R 3 is a methyl group. R in the above formula (1) 4 is preferably a hydrogen atom or a hydrocarbon group having 1 to 18 carbon atoms, more preferably a hydrogen atom or a hydrocarbon group having 1 to 8 carbon atoms, even more preferably a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms, and particularly preferably a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms. Examples of the hydrocarbon group include an alkyl group (linear, branched or cyclic), a phenyl group, an alkyl-substituted phenyl group, etc. Among these, an alkyl group (linear, branched or cyclic) is preferred, a methyl group, an ethyl group, a propyl group are more preferred, and a methyl group is most preferred. In the above formula (1), R 5 O represents an oxyalkylene group having 2 to 18 carbon atoms, which may be the same or different, and is represented by n R 5 This means that all the oxyalkylene groups of O may be the same or different. The preferred ranges of the carbon number and the like of the oxyalkylene group are as described above. In the above formula (1), n ​​is preferably 2-200, and more preferably 2-150. In the above formula (1), when y is 0, x is preferably 1 to 4, more preferably 1 or 2, and even more preferably 2. When x is 1 to 4, R 3 is preferably a methyl group. In the above formula (1), when y is 1, x is preferably 0. In this case, R 3 is more preferably a hydrogen atom or a methyl group.

[0026] Specific examples of the (poly)alkylene glycol monomer include polyalkylene glycol (meth)acrylates such as polyethylene glycol (meth)acrylate, and alkoxy polyalkylene glycol (meth)acrylates obtained by hydrophobically modifying these terminals with a hydrocarbon group having 1 to 30 carbon atoms; compounds obtained by adding 1 to 300 moles of alkylene oxide to unsaturated alcohols having 2 to 8 carbon atoms, such as vinyl alcohol, allyl alcohol, methallyl alcohol, 3-methyl-3-buten-1-ol, 3-methyl-2-buten-1-ol, 2-methyl-3-buten-1-ol, 2-methyl-2-buten-1-ol, and 3-allyloxy-1,2-propanediol, and compounds obtained by hydrophobically modifying these terminals with a hydrocarbon group having 1 to 30 carbon atoms. The compound in which 1 to 300 moles of an alkylene oxide is added to an unsaturated alcohol having 2 to 8 carbon atoms is preferably a compound in which an alkylene oxide is added to 4-hydroxybutyl-1-monovinyl ether, (meth)allyl alcohol, or 3-methyl-3-buten-1-ol.

[0027] The polycarboxylic acid polymer and polycarboxylic acid ether polymer may be copolymerized with a copolymerizable monomer other than the unsaturated carboxylic acid monomer and the (poly)alkylene glycol monomer. Specific examples of other copolymerizable monomers include 3-(meth)allyloxy-2-hydroxypropanesulfonic acid, 2-(meth)allyloxyethylenesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, p-styrenesulfonic acid, α-methyl-p-styrenesulfonic acid, vinylsulfonic acid, vinylsulfamic acid, (meth)allyl sulfonic acid, isoprene sulfonic acid, 4-(allyloxy)benzenesulfonic acid, 1-methyl-2-propene-1-sulfonic acid, 1,1-dimethyl-2-propene-1-sulfonic acid, 3-butene unsaturated sulfonic acids and their salts, such as 1-butene-1-sulfonic acid, 1-butene-3-sulfonic acid, 2-acrylamido-1-methylpropanesulfonic acid, 2-acrylamidopropanesulfonic acid, 2-acrylamido-n-butanesulfonic acid, 2-acrylamido-2-phenylpropanesulfonic acid, and 2-((meth)acryloyloxy)ethanesulfonic acid; hydroxyl-containing ethers, such as 3-(meth)allyloxy-1,2-dihydroxypropane and 1-allyloxy-3-butoxypropan-2-ol; N-vinylpyrrolidone and other N-vinyl lactam monomers; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, iso-nonyl (meth)acrylate, dodecyl (meth)acrylate, and stearyl (meth)acrylate; hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3- Hydroxyl group-containing (meth)acrylic acid esters such as hydroxypropyl (meth)acrylate, 2-hydroxy-1-methylethyl (meth)acrylate, 2-hydroxybutyl acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and hydroxypentyl (meth)acrylate; N-substituted or unsubstituted (meth)acrylamides such as (meth)acrylamide, N-monomethyl (meth)acrylamide, N-monoethyl (meth)acrylamide, and N,N-dimethyl (meth)acrylamide;Examples of the vinyl aryl monomers include styrene, α-methylstyrene, vinyltoluene, indene, vinylnaphthalene, phenylmaleimide, and vinylaniline; alkenes such as ethylene, propylene, butadiene, isobutylene, and octene; vinyl carboxylates such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, and butyl vinyl ether; vinyl ethylene carbonate and its derivatives; unsaturated amines such as N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylamide, vinylpyridine, vinylimidazole, and salts or quaternary derivatives thereof; and vinyl cyanide monomers such as acrylonitrile and methacrylonitrile.

[0028] Examples of the phosphoric acid polymer include phosphoric acid polymers containing a polyalkylene glycol group and phosphoric acid condensates. The phosphoric acid polymer is preferably a polymer obtained by copolymerizing a monomer component containing a (poly)alkylene glycol monomer and a phosphoric acid monomer. Examples of the phosphoric acid monomer include mono(2-hydroxyethyl)(meth)acrylic acid ester, di-{(2-hydroxyethyl)(meth)acrylic acid} ester, and (poly)alkylene glycol mono(meth)acrylate acid phosphate. As the phosphoric acid condensate, for example, a condensate of a phosphoric acid ester and an aldehyde compound is suitable. The phosphoric acid ester is not particularly limited as long as it is an esterification product of phosphoric acid (which may be a salt) and a hydroxyl group-containing compound, and one or more kinds can be used. In addition, any of phosphoric acid monoester, phosphoric acid diester, and phosphoric acid triester may be used.

[0029] Examples of surfactant-type dispersants include anionic surfactant-type dispersants such as alkylsulfonic acid-based dispersants, cationic surfactant-type dispersants such as quaternary ammonium-based and alkylpolyamine-based dispersants, and nonionic surfactant-type dispersants such as higher alcohol alkylene oxide-based and polyhydric alcohol ester-based dispersants. Examples of inorganic dispersants include anionic inorganic dispersants such as polyphosphates (for example, sodium tripolyphosphate). These dispersants may be used alone or in combination.

[0030] The amount of the dispersant in the above composition (if used) is not particularly limited, but from the viewpoint of dispersing the hydraulic material well in the slurry and from the viewpoint of the balance between this effect and efficiency and economy, for example, it is 0.01 parts by mass or more and 4 parts by mass or less, preferably 0.01 parts by mass or more and 3 parts by mass or less, 0.01 parts by mass or more and 2 parts by mass or less, 0.01 parts by mass or more and 1 part by mass or less, 0.01 parts by mass or more and 0.8 parts by mass or more and 0.01 parts by mass or more and 0.5 parts by mass or less, 0.012 parts by mass or more and 0.01 ... 0.012 parts by mass to 3 parts by mass, 0.012 parts to 2 parts by mass, 0.012 parts to 1 part by mass, 0.012 parts to 0.8 parts by mass, 0.012 parts to 0.5 parts by mass, 0.015 parts by mass The amount may be at least 0.015 parts by mass and at most 3 parts by mass, at least 0.015 parts by mass and at most 2 parts by mass, at least 0.015 parts by mass and at most 1 part by mass, at least 0.015 parts by mass and at most 0.8 parts by mass, or at least 0.015 parts by mass and at most 0.5 parts by mass.

[0031] Hardening inhibitors In one embodiment of the space filling method according to the present invention, the hardening inhibitor that can be selected as one component of the composition has the function of inhibiting and delaying the early hardening reaction between the hydraulic material in the slurry and carbon dioxide. By including the hardening inhibitor in the composition, when the slurry of the composition is injected together with carbon dioxide to fill a space, early hardening before the slurry reaches the entire space is suppressed, and it becomes easier to efficiently fill and solidify every corner of the space, especially including at least partially narrowed or complicated shapes.

[0032] Examples of hardening inhibitors include, but are not limited to, oxycarboxylic acids or salts thereof such as gluconic acid, glucoheptonic acid, arabinic acid, tartaric acid, malic acid, and citric acid; keto acids or salts thereof such as pyruvic acid, oxaloacetic acid, α-ketoglutaric acid, acetoacetic acid, acetone dicarboxylic acid, levulinic acid, propionylacetic acid, and benzoylacetic acid; monosaccharides such as glucose, fructose, galactose, saccharose, xylose, apiose, ribose, and isomerized sugar; oligosaccharides such as disaccharides and trisaccharides, oligosaccharides such as dextrin, and polysaccharides such as dextran; sugars such as molasses containing these; sugar alcohols such as sorbitol; polyhydric alcohols such as glycerin; magnesium silicofluoride; and boric acids. These hardening inhibitors can be used alone or in mixtures of multiple types. The hardening inhibitor preferably contains at least one selected from the group consisting of oxycarboxylic acid or its salt, keto acid or its salt, sugar, and sugar alcohol. It is more preferable to contain oxycarboxylic acid or its salt that also acts as a chelating agent (metal eluting agent) described later.

[0033] The amount of the set inhibitor in the above composition (if used) is not particularly limited, but from the viewpoint of sufficiently imparting the function of inhibiting and delaying the set reaction of the hydraulic material in the slurry while at the same time not excessively stopping the set reaction, for example, it is 0.04 parts by mass or more and 4 parts by mass or less, preferably 0.04 parts by mass or more and 3 parts by mass or less, 0.04 parts by mass or more and 2 parts by mass or less, 0.04 parts by mass or more and 1 part by mass or less, 0.04 parts by mass or more and 0.8 parts by mass or less, 0.04 parts by mass or more and ... 5 parts by mass or less, 0.06 parts by mass or more and 4 parts by mass or less, 0.06 parts by mass or more and 3 parts by mass or less, 0.06 parts by mass or more and 2 parts by mass or less, 0.06 parts by mass or more and 1 part by mass or less, 0.06 parts by mass or more and 0.8 parts by mass or less, 0.06 parts by mass or more and 0.5 parts by mass or less, 0 The amount may be .07 parts by weight or more and 4 parts by weight or less, 0.07 parts by weight or more and 3 parts by weight or less, 0.07 parts by weight or more and 2 parts by weight or less, 0.07 parts by weight or more and 1 part by weight or less, 0.07 parts by weight or more and 0.8 parts by weight or less, or 0.07 parts by weight or more and 0.5 parts by weight or less.

[0034] Chelating agents (metal eluting agents) In one embodiment of the space filling method according to the present invention, a chelating agent (which may also be referred to as a metal eluting agent) that may be selected as one component of the composition functions to elute metal ions into the slurry by chelating the metals that constitute the hydraulic material in the slurry of the composition. By including a chelating agent (metal eluting agent) in the composition, when the slurry of the composition is injected together with carbon dioxide to fill a space, the reaction between the metal and carbon dioxide is promoted by eluting the metal ions that constitute the hydraulic material, and the amount of carbon dioxide fixed during filling the space can be increased.

[0035] The chelating agent (metal eluting agent) is not particularly limited, but examples thereof include ethylenediaminetetraacetic acid (EDTA), nitrilotriacetic acid (NTA), hydroxyethyliminodiacetic acid (HIDA), hydroxyethylethylenediaminetriacetic acid (HEDTA), diethylenetriaminepentaacetic acid (DTPA), triethylenetetraminehexaacetic acid (TTHA), 1,3-propanediaminetetraacetic acid (PDTA), dihydroxyethylethylenediaminediacetic acid (DHEDDA), 1,3-diamino-2-hydroxypropane-tetraacetic acid (DPTA-OH), dihydroxyethyl Aminocarboxylic acid chelating agents such as glycine (DHEG), glycol ether diamine tetraacetic acid (GEDTA), dicarboxymethyl glutamic acid (CMGA), ethylenediamine-N,N'-disuccinic acid (EDDS), 3-hydroxy-2,2'-iminodisuccinic acid (HIDS) and their metal (sodium, potassium, etc.) salts; hydroxyethylidene diphosphonic acid (HEDP), nitrilotris(methylene phosphonic acid) (NTMP), phosphonobutane tricarboxylic acid (PBTC), ethylenediaminetetra(methylene phosphonic acid) (EDTMP) Examples of suitable chelating agents include phosphonic acid chelating agents such as diethylenetriaminepenta(methylenephosphonic acid) (DTPMP) and their metal (sodium, potassium, etc.) salts; β-diketones such as acetylacetone, benzoylacetone, stearoylacetone, stearoylbenzoylmethane, dibenzoylmethane, etc.; oxyphenols such as catechol and pyrogallol; amino alcohols such as diethanolamine and triethanolamine; amino acids such as glycine and alanine; humic acid; tannic acid; condensed phosphates, etc. These chelating agents can be used alone or in combination. As the chelating agent, aminocarboxylic acid-based chelating agents and phosphonic acid-based chelating agents are preferred.

[0036] The amount of the chelating agent (metal eluting agent) in the above composition (if used) is not particularly limited, but from the viewpoint of sufficiently promoting the elution of metals from the hydraulic material in the slurry, and from the viewpoint of the balance between this effect and efficiency and economy, it is, for example, 0.04 parts by mass or more and 4 parts by mass or less, preferably 0.04 parts by mass or more and 3 parts by mass or less, 0.04 parts by mass or more and 2 parts by mass or less, 0.04 parts by mass or more and 1 part by mass or less, 0.04 parts by mass or more and 0.8 parts ... 0.5 parts by mass or less, 0.06 parts by mass or more and 4 parts by mass or less, 0.06 parts by mass or more and 3 parts by mass or less, 0.06 parts by mass or more and 2 parts by mass or less, 0.06 parts by mass or more and 1 part by mass or less, 0.06 parts by mass or more and 0.8 parts by mass or less, 0.06 parts by mass or more and 0.5 parts by mass or less, The amount may be from 0.07 parts by mass to 4 parts by mass, from 0.07 parts by mass to 3 parts by mass, from 0.07 parts by mass to 2 parts by mass, from 0.07 parts by mass to 1 part by mass, from 0.07 parts by mass to 0.8 parts by mass, or from 0.07 parts by mass to 0.5 parts by mass.

[0037] In one embodiment, the amount of water contained in the slurry of the composition is not particularly limited, but from the viewpoint of ensuring the fluidity of the slurry when it is injected into the space and the balance between the effectiveness and efficiency of the hardening reaction, the amount of water is usually 5 parts by mass or more and 500 parts by mass or less, preferably 5 parts by mass or more and 400 parts by mass or less, 5 parts by mass or more and 300 parts by mass or less, 5 parts by mass or more and 200 parts by mass or less, 5 parts by mass or more and 100 parts by mass or less, 10 parts by mass or more and 500 parts by mass or less, 10 parts by mass or more and 400 parts by mass or less, 10 parts by mass or more and 300 parts by mass or less, 10 parts by mass or more and 200 parts by mass or less, 10 parts by mass or more and ... 00 parts by mass or less, 20 parts by mass or more and 500 parts by mass or less, 20 parts by mass but not more than 400 parts by mass, 20 parts by mass but not more than 300 parts by mass, 20 parts by mass but not more than 200 parts by mass, 20 parts by mass but not more than 100 parts by mass, 30 parts by mass but not more than 500 parts by mass, 30 parts by mass but not more than 400 parts by mass, 30 parts by mass or less 00 parts by weight or less, 30 parts by weight but not more than 200 parts by weight, 30 parts by weight but not more than 100 parts by weight, 40 parts by weight or more and not more than 500 parts by weight, 40 parts by weight and not more than 400 parts by weight, 40 parts by weight and not more than 300 parts by weight, 40 parts by weight and not more than 200 parts by weight, or 40 parts by weight and not more than 100 parts by weight.

[0038] The slurry of the composition can be obtained by stirring and mixing the above essential hydraulic materials and, if necessary, optional components and water in a predetermined ratio. Stirring and mixing can usually be performed at room temperature, but may also be performed at, for example, 5°C to 50°C. The stirring and mixing time is not particularly limited, but may be 10 seconds to 1 hour, typically 20 seconds to 40 minutes.

[0039] Geopolymer In one embodiment, a geopolymer slurry can be formed by mixing an aluminosilicate material (active filler) such as blast furnace slag or fly ash as a hydraulic material, water, and, if necessary, other alkaline stimulants such as sodium hydroxide (NaOH) in the presence of sodium silicate (water glass). By using such a geopolymer slurry, CO2 emissions can be significantly reduced compared to when cement is used as a hydraulic material, and the hardened product has the advantages of being excellent in acid resistance and fire resistance. The mechanism of the hardening reaction of geopolymer is shown in the following formula. This reaction is polymerization by condensation polymerization. The bonds of Si and Al contained in the aluminosilicate material are destroyed by alkaline stimulation, and the Ca 2+ OrNa + Metal ions such as OH and metal ions react with each other to form monomers. These monomers dehydrate and bond with metal ions to form polymers and harden. At the same time, these metal ions react with carbon dioxide to form a hardened material, and the combination of these reactions results in the formation of a strong composite hardened material. [ka]

[0040] Hardened geopolymers have better fire resistance and acid resistance than hardened cement, which is thought to be because the chemical composition of the active filler produces products different from cement hydrates. Aluminosilicate materials such as blast furnace slag and fly ash, which are commonly used as binders for geopolymers, have less Ca content than Portland cement, so they are less likely to turn into gypsum when exposed to acid, making them more acid-resistant. In addition, because the main component of geopolymers is an amorphous gel, they also have the advantage of being less prone to strength loss due to exposure to heat and having excellent high-temperature resistance.

[0041] Slurry characteristics The slurry of the composition may take, after production of the slurry, for the hydraulic material, water, and carbon dioxide to completely lose fluidity and harden in a time period of usually 1 hour or more, preferably 3 hours or more, more preferably 5 hours or more, even more preferably 10 hours or more, even more preferably 15 hours or more, and most preferably 24 hours (1 day) or more or more than 24 hours (1 day). Here, a state in which the composition slurry has not "completely lost fluidity and hardened" means that, after a specified period of time has elapsed since the slurry of the composition was poured into a specified mold at 20°C and contacted with carbon dioxide (at a concentration of at least 80%) in a closed system, the slurry cannot be removed from the mold at all (the adhesion of the slurry to the inner surface of the mold is still maintained), or the slurry cannot be removed in a clean state in which substantially all of the shape of the inner surface of the mold is reflected in the outer shape of the cured product (for example, since not all parts have hardened, it is unavoidable that some of the cured product will be damaged when removed from the mold).

[0042] Space filling method The space filling method according to the present invention includes injecting a slurry containing the above-mentioned composition into a space and causing the composition to react with carbon dioxide injected into the space together with the slurry or with carbon dioxide injected into the space separately from the slurry, thereby filling the space. The space intended to be filled by the space filling method of the present invention is not particularly limited and includes spaces having any shape and volume (capacity). In addition, the space includes spaces existing above ground and spaces existing underground (for example, holes in the earth layer, underground tunnels, coal mining sites, etc.). The volume of the space to be buried is not limited, but may be, for example, 10 -3 m 3 ~10 7 m 3 Typically, 1 m 3 ~10 6 m 3 , 1m 3 ~10 5 m 3 , 5m 3 ~10 4 m 3 , 5m 3 ~10 3 m 3 , or 10m 3 ~10 3 m 3 It may be.

[0043] The carbon dioxide source used in the spatial burial method according to the present invention is not particularly limited. In one embodiment, the carbon dioxide used in the present method includes carbon dioxide discharged and recovered from various chemical plants such as power plants, oil refineries, and ammonia production facilities.

[0044] The pressure at which the carbon dioxide is injected into the space can be determined depending on various factors such as the form of the carbon dioxide, the diameter and length of the conduit from the inlet to the space, the shape and volume of the space to be buried, etc. The pressure at which the carbon dioxide is injected is not particularly limited, and may be, for example, above atmospheric pressure and not more than 100 MPaG, typically from 1 MPaG to 50 MPaG, from 2 MPaG to 40 MPaG, or from 3 MPaG to 30 MPaG.

[0045] An example of a space is an underground coal mine site or tunnel in an underground coal mine. Another example of a space is underground buried pipes for various purposes such as sewerage, water supply, gas, electricity, communication, and water, which are no longer used due to deterioration or damage. In particular, such underground coal mine sites and tunnels in closed coal mines, or buried underground pipes that have deteriorated or been damaged, often have partially narrowed or complicated spaces to be filled, such as deformation or submersion of underground cavities. For example, in the space in an underground coal mine site, in addition to a certain degree of continuous wide space, there are also spaces where extremely narrow passages filled with crushed stones, pebbles, etc. are intricately connected. In addition, such underground coal mine sites and tunnels in underground coal mines may be several hundred meters to more than 1,000 meters deep underground. According to the space embedding method of this embodiment, carbon dioxide, which is a greenhouse gas, can be efficiently filled and solidified into every corner of the space together with a solidifying material having suitable fluidity and solidifying properties, while suppressing solidification near an injection port in a space, particularly a space including at least a partially narrowed or complicated shape, to embed the space. In addition, the embedding efficiency and strength of the space can be increased, and a larger amount of carbon dioxide can be fixed and mineralized, which contributes to the prevention of global warming and environmental conservation.

[0046] In one embodiment, when carbon dioxide and the slurry of the composition are injected into a space, the carbon dioxide and the slurry of the composition are mixed in advance before being introduced into the space, that is, the carbon dioxide and the slurry of the composition can share a common path to the space. In a more preferred embodiment, when carbon dioxide and the slurry of the composition are injected into the space, the carbon dioxide and the slurry of the composition are introduced into the space through separate paths without mixing the carbon dioxide and the slurry of the composition in advance, and the reaction occurs only when the carbon dioxide and the slurry reach the space, so that the filling of the slurry of the composition and the fixation of carbon dioxide can be achieved. The separate paths include a case where one conduit is used with a time lag, and a case where two (or three or more) separate conduits are used. In this embodiment, it is preferable to first fill the space to be filled with the slurry of the composition, and then introduce carbon dioxide, thereby preventing premature solidification, reliably filling the space, and fixating a larger amount of carbon dioxide. In any embodiment, as long as the slurry of the composition reaches every corner of the space to be buried after it is contacted with carbon dioxide after the slurry is produced, i.e., after the hydraulic material, water, and carbon dioxide start to contact each other, and before it completely loses fluidity and hardens, the supply conditions such as the supply speed (flow rate) and supply pressure of the slurry to the space can be appropriately adjusted. The supply speed of the slurry to the space is not limited in any way, but is preferably, for example, 10 -3 m 3 / min~5·10 3 m 3 / min, typically 10 -3 m 3 / min~10 3 m 3 / min, 10 -3 m 3 / min~10 2 m 3 / min, 10 -2 m 3 / min~10 3 m 3 / min, 10 -2 m 3 / min~10 2 m 3 / min, 10 -1 m 3 / min~10 2 m 3 / min, or 10 -1 m 3 / min~10m 3 / min.

[0047] The carbon dioxide injected into the space dissolves in the water in the slurry to become carbonate ions or hydrogen carbonate ions. The carbonate ions or hydrogen carbonate ions combine with metal ions, such as calcium ions, originating from the hydraulic material to generate solid metal carbonate salts (e.g., calcium carbonate), thereby fixing the carbon dioxide. The carbon dioxide injected into the space is not limited to gaseous carbon dioxide, and may be carbon dioxide in a supercritical state. Considering various factors such as the position, shape, and size of the space to be buried, and the type and amount of the hydraulic material and optional components of the slurry, the properties of the carbon dioxide used can be appropriately selected from the viewpoint of the handling and efficiency of the injection and fixation of carbon dioxide. As the carbon dioxide gas, gas from liquid carbon dioxide, compressed carbon dioxide gas, gas from dry ice, carbon dioxide gas generated by a chemical reaction, etc. can be used. The concentration of the carbon dioxide gas injected is preferably 75% or more, more preferably 80% or more, even more preferably 85% or more, even more preferably 90% or more, and most preferably 95% or more.

[0048] For example, if carbon dioxide injected into a space reacts with calcium ions to produce calcium carbonate, theoretically the 3 Carbon dioxide gas (25°C, atmospheric pressure; mass approximately 1.98 kg) reacts with approximately 2.26 kg of calcium oxide. In other words, it is understood that this reaction allows carbon dioxide gas to be absorbed and fixed with a small amount of calcium component.

[0049] The amount of carbon dioxide that is buried in a space and fixed / mineralized by the space burying method of any of the above embodiments depends on the type and amount of hydraulic material and other optional components used in the slurry, the hardening reaction rate determined by them, and also on the procedure for supplying the slurry and carbon dioxide to the space, and is not particularly limited. In one embodiment, the degree to which the composition slurry is immobilized through a curing reaction with carbon dioxide is measured by introducing the slurry and a saturated amount of carbon dioxide into a closed system, and measuring the amount of carbon dioxide adsorbed per unit volume of the slurry after, for example, 30 minutes (amount of carbon dioxide reduced in the system: kg / m 3 The amount of carbon dioxide adsorption 30 minutes after the composition slurry starts to come into contact with carbon dioxide is preferably 50 kg / m 3 More preferably, it is 100 kg / m 3 More preferably, 200 kg / m 3 More than 300 kg / m 3 It may be more than that.

[0050] Furthermore, the amount of carbon dioxide that is buried in the space and fixed / mineralized can be determined by subjecting the product of the hardening reaction between metal ions derived from hydraulic materials and carbon dioxide (e.g. calcium carbonate: CaCO3) to thermogravimetric differential thermal analysis (TG-DTA) and analyzing the amount of carbon dioxide:CO2 fixed per unit weight of the product (i.e., the percentage of weight lost by thermogravimetric differential thermal analysis). When the product of the hardening reaction between metal ions derived from hydraulic materials and carbon dioxide is calcium carbonate (CaCO3), the decomposition temperature is approximately 230°C to approximately 730°C, so it is sufficient to subject it to thermogravimetric differential thermal analysis between these temperatures and analyze the percentage of weight lost per unit weight of the product. In other words, the amount of carbon dioxide fixed at this time (%)W CO2 can be calculated by the following formula, where m0 (mg) is the mass of the product sample of the hardening reaction minus the mass of free water, and m1 (mg) is the mass decreased within a certain temperature range by thermogravimetric differential thermal analysis (for calcium carbonate, the mass decreased between about 230°C and about 730°C: that is, the mass of carbon dioxide generated by the thermal decomposition of calcium carbonate). W CO2 =(m1 / m0)×100(%)

[0051] The amount of carbon dioxide that is buried in the space and fixed and mineralized is the amount of carbon dioxide fixed W14 days (i.e., 2 weeks) after the slurry (containing hydraulic materials, optional ingredients, and water) starts to come into contact with carbon dioxide. CO2 is preferably 2.0% or more, more preferably 4.0% or more, even more preferably 5.0% or more, even more preferably 6.0% or more, even more preferably 7.0% or more, and most preferably 8.0% or more.

[0052] In a preferred embodiment, it is also preferable to provide a discharge pipe for unreacted (unfixed) carbon dioxide among the carbon dioxide injected into the space. When the space to be buried is a substantially closed system, the substantial amount of carbon dioxide fixed can be measured from the difference and fluctuation between the amount of carbon dioxide injected and the amount of carbon dioxide discharged, and the time-dependent change in the carbon dioxide fixation ability of the hydraulic material can be understood. In such a case, when the carbon dioxide concentration in the exhaust gas reaches a predetermined threshold value, for example, 80% or more or 90%, it is possible to determine that the carbon dioxide fixation ability of the hydraulic material is close to saturation, and therefore to stop the injection of carbon dioxide.

[0053] Figure 1 is a schematic diagram of an embodiment of the spatial burial method or spatial burial system according to the present invention, applied to the site of underground coal mining in an underground coal mine. Please note that this is a non-limiting example. In Figure 1, 1 is the spatial burial system, 2 is a carbon dioxide storage facility, 3 is a carbon dioxide injection well, 4 is a carbon dioxide injection pipe, 5 is an underground aquifer, 6 is a coal seam, 7 is the site of underground coal mining in an underground coal mine, and 8 is the space to be buried. Carbon dioxide (e.g., liquefied matter or supercritical fluid) discharged and recovered from various chemical plants such as power plants, oil refineries, or ammonia manufacturing facilities is temporarily stored in a storage facility 2 such as a tank, and then injected and filled from a carbon dioxide injection well 3 toward a space 8 to be buried through an injection pipe 4. The injection port of the carbon dioxide injection well 3 may usually be equipped with a pump for reliably sending carbon dioxide to the space. The underground coal mine site 7 of an underground coal mine is often installed deep underground, for example, at a depth of several hundred meters to more than 1000 meters underground. In such cases, the carbon dioxide injection pipe 4 is arranged to pass through an underground aquifer 5 to the underground coal mine site 7 of an underground coal mine located in a coal seam 6 and the space 8 to be buried therein.

[0054] Preferably, prior to injecting and filling the carbon dioxide into the space 8, a slurry of a composition containing a hydraulic material is fed and filled into the space 8. Although a conduit for feeding the composition slurry into the space 8 is not shown, the conduit may be common to the conduit 4 for injecting carbon dioxide, or may be provided separately. The injection speed of carbon dioxide (and pump pressure) into the space 8 and the feeding speed of the composition slurry are not particularly limited, as long as the composition slurry reaches every corner of the space to be buried before the composition slurry completely loses fluidity and hardens after contact with carbon dioxide. Preferably, when carbon dioxide and the composition slurry are injected into the space, the composition slurry is first introduced into the space to be buried through a route separated (in time or physically) without mixing the carbon dioxide and the composition slurry in advance, and then carbon dioxide is introduced into the space, and they are configured to react only when they reach the space, thereby achieving filling of the composition slurry and fixation of carbon dioxide. According to this embodiment, the solidification of the composition slurry near the injection port in a space including a shape that is at least partially narrowed or complicated can be suppressed, and the space can be filled and solidified efficiently to every corner, thereby increasing the efficiency and strength of the space to be buried and enabling fixation and mineralization of a larger amount of carbon dioxide, which can contribute to the prevention of global warming and environmental conservation. EXAMPLES

[0055] The effects of the present invention will be described in more detail below based on examples, although the present invention is not limited to these examples.

[0056] Substances used (1) Hydraulic material (binder) Blast furnace slag powder: "Spirits 4000" (product name) manufactured by Nippon Steel Cement Co., Ltd. Density 2.91g / cm 3 , specific surface area 4050cm 2 / g Fly ash: Produced by Hokuden Kogyo Co., Ltd. Composition - SiO2:58.4%, Al2O3:23.2%, Fe2O3:5.9%, CaO:3.7%, SO3:1.0%, MgO:0.8%

[0057] (2) Alkaline stimulants Sodium Hydroxide (3) Dispersants "JW-7" (Polycarboxylate ether polymer) "MJ-3" (Polycarboxylic acid polymer) (4) Chelating agents (metal eluting agents) "CY-1" (also functions as a dispersant) (5) Hardening inhibitors "KS-1" (Sodium gluconate)

[0058] Example 1 Blast furnace slag was used as the hydraulic material (binder), and the mass ratio of water to blast furnace slag (W / B) was 0.35. Blast furnace slag and water were placed in a beaker. Then, in an environment of 20°C, they were mixed in a mixer for 1 minute, scraped off for 1 minute, and further mixed in a mixer for 4 minutes to obtain composition slurry 1. Then, this composition slurry 1 was cured in a carbon dioxide (CO2) accelerated environment (i.e., in an environment of 100% carbon dioxide) to obtain composition slurry 1' into which carbon dioxide was injected.

[0059] Example 2 Composition slurry 2 and composition slurry 2' into which carbon dioxide had been injected were obtained in the same manner as in Example 1 above, except that sodium hydroxide was also added to the beaker as an alkaline stimulant in an amount such that the mass ratio (Na2O / B) of Na2O from sodium hydroxide (NaOH) to the hydraulic material (binder) was 0.045, in addition to the blast furnace slag and water as the hydraulic material (binder).

[0060] Example 3 Composition slurry 3 and composition slurry 3' into which carbon dioxide had been injected were obtained in the same manner as in Example 1 above, except that blast furnace slag and water were placed in a beaker such that the mass ratio (W / B) of water to blast furnace slag as a hydraulic material (binder) was 0.5, and sodium hydroxide was also added to the beaker as an alkaline stimulant in an amount such that the mass ratio (Na2O / B) of Na2O from sodium hydroxide (NaOH) to the hydraulic material (binder) was 0.09.

[0061] Example 4 Composition slurry 4 and composition slurry 4' into which carbon dioxide had been injected were obtained in the same manner as in Example 1 above, except that fly ash was used as the hydraulic material (binder), and the mass ratio of water to fly ash (W / B) was set to 0.4, and fly ash and water were placed in a beaker. In addition, sodium hydroxide was also added to the beaker as an alkaline stimulant in an amount such that the mass ratio (Na2O / B) of Na2O from sodium hydroxide (NaOH) to the hydraulic material (binder) was 0.148.

[0062] Example 5 Composition slurry 5 and composition slurry 5' into which carbon dioxide had been injected were obtained in the same manner as in Example 1 above, except that fly ash was used as the hydraulic material (binder), and fly ash and water were placed in a beaker with a mass ratio of water to fly ash (W / B) of 0.5. In addition, sodium hydroxide was also added to the beaker as an alkaline stimulant in an amount such that the mass ratio (NaO / B) of Na2O from sodium hydroxide (NaOH) to the hydraulic material (binder) was 0.185.

[0063] (i) Measurement of fluidity (flow characteristics) of composition slurry For each of the composition slurries 1 to 5, the fluidity (flow characteristics) was measured after stirring for 5 minutes at room temperature (about 20° C.). Fluidity was measured according to JIS-R-5201 "Physical Testing Methods for Cement." Using a flow table, flow cone, and poker, the composition slurry sample was packed into the flow cone in two layers, one half at a time. Each layer was poked evenly 15 times, and the paste was given a falling motion, and the direction in which the diameter of the slurry after spreading was found to be the largest and the direction perpendicular to this were measured, which were taken as the flow value. If a falling motion was not possible, a flat plate for slump testing was used, and measurements were taken 30 seconds after the flow cone was lifted.

[0064] (ii) Measurement of the compressive strength of the composition slurry after curing for 14 days under a carbon dioxide atmosphere After each of the composition slurries 1 to 5 was formed, the composition slurries were mixed for 1 minute, scraped off for 1 minute, and then mixed for another 4 minutes. A cylindrical plastic mold with a diameter of φ50×100 (mm) was used as the mold. The mixed slurry was divided into two layers and poured into the mold, and each layer was struck 15 times with a ram, then struck with a mallet and smoothed with a trowel. The slurry introduced into the formwork in this way was cured for 14 days at room temperature (approximately 20°C) in an atmosphere of 80% or more carbon dioxide, and the compressive strength was measured in accordance with the JIS A1108 concrete compression test method. The samples were removed from the form when they were one day old and cured. Samples that could not be removed from the form within one day (after 24 hours), in other words, samples where the slurry's adhesion to the inner surface of the formwork was still maintained, were cured without being removed from the form. After curing for 14 days in a carbon dioxide atmosphere, the casting surface was polished to ensure that the load was applied evenly. A load was applied evenly using a compressive strength tester, but not enough to cause impact, at a loading rate of 0.6±0.4 (N / mm) per second. 2 The compressive strength was calculated by reading the maximum load indicated by the testing machine when the target sample was broken down to 0.5 (kN) and dividing this by the cross-sectional area of ​​the sample. Here, if the mixed slurry cannot be demolded one day (after 24 hours) from the start of curing in a carbon dioxide atmosphere, that is, if the slurry still retains its adhesion to the inner surface of the formwork, or if the mixed slurry cannot be demolded in such a clean state that substantially all of the inner surface shape of the formwork is reflected in the outer shape of the hardened product (for example, if not all parts are hardened, it is impossible to avoid damage to a part of the hardened product when demolded), then the mixed slurry can be judged to be "unhardened". Conversely, if the mixed slurry can be demolded one day (after 24 hours) from the start of curing in a carbon dioxide atmosphere, that is, if the slurry still retains its adhesion to the inner surface of the formwork, or if the mixed slurry can be demolded in such a clean state that substantially all of the inner surface shape of the formwork is reflected in the outer shape of the hardened product, then the mixed slurry can be judged to be "hardened".

[0065] (iii) The amount of carbon dioxide fixed and calcium carbonate (CaCO) of the composition slurry after curing for 14 days under a carbon dioxide atmosphere 3 ) Measurement of the amount of production The sample obtained after 14 days of curing under a carbon dioxide atmosphere in (ii) above was immersed in isopropanol for 15 minutes, suction filtered for 1 minute, and pretreated by drying in a 40°C chamber for 7 minutes. The amount of the measurement sample was 10±1 mg, and the temperature was raised at 20°C / min under a nitrogen atmosphere, and after reaching 1000°C, it was maintained for 5 minutes, and then cooled. Under these conditions, thermogravimetric differential thermal analysis (TG-DTA) was performed to grasp the amount of fixed carbon dioxide. When the product of the hardening reaction between metal ions derived from hydraulic materials and carbon dioxide is calcium carbonate (CaCO3), the decomposition temperature is about 230°C to about 730°C, so that the amount of fixed carbon dioxide (%) and even the amount of calcium carbonate (CaCO3) generated (%) can be quantified by analyzing the ratio of the weight loss per unit weight of the product. Carbon dioxide fixation (%)W CO2 can be calculated using the following formula, where m0 (mg) is the mass of the sample (the product of the hardening reaction between the hydraulic material of the slurry and carbon dioxide) minus the mass of free water, and m1 (mg) is the mass lost within the above temperature range in thermogravimetric differential thermal analysis (for calcium carbonate, the mass lost between approximately 230°C and approximately 730°C: i.e., the mass of carbon dioxide generated by the thermal decomposition of calcium carbonate). W CO2 =(m1 / m0)×100(%) In addition, the amount of calcium carbonate (CaCO3) generated (%) W CaCO3 The mass ratio of calcium carbonate in the sample after aging treatment can be calculated from the thermal decomposition reaction formula CaCO3 (molecular weight 100) → CaO (molecular weight 56) + CO2 (molecular weight 44) using the following formula. W CaCO3 =W CO2 ×(100 / 44)(%) Furthermore, from the amount of CaCO3 produced, the amount of CO2 fixed per slurry volume (kg / m 3 ) was calculated.

[0066] The measurement results of the above physical properties (i) to (iii) for Composition Slurries 1 to 5 (Examples 1 to 5) are shown in Table 1 below, together with the mass ratio of water to hydraulic material (binder) (W / B) and the mass ratio of Na2O from sodium hydroxide (NaOH) of the alkaline irritant to the hydraulic material (binder) (Na2O / B).

[0067] [Table 1]

[0068] From the results shown in Table 1, it can be understood that according to the space filling method of the present invention, by adjusting the type and amount of hydraulic material of the composition and the presence or absence or amount of an alkaline irritant, it is possible to control the fluidity and hardening speed within an appropriate range, thereby efficiently filling the space, and at the same time, to fill and solidify a larger amount of carbon dioxide.

[0069] Example 6 Blast furnace slag was used as the hydraulic material (binder), and the mass ratio of water to blast furnace slag (W / B) was 0.35. Blast furnace slag and water were placed in a beaker, and dispersant "JW-7" was added at a mass ratio (solid content equivalent) of 0.018 mass% relative to the blast furnace slag. Composition slurry 6 was obtained by mixing by hand at room temperature (approximately 20°C) for 30 seconds.

[0070] Example 7 Composition slurry 7 was obtained in the same manner as in Example 6, except that the dispersant "JW-7" was replaced with a chelating agent "CY-1" (which also functions as a dispersant) at a mass ratio (solid content equivalent) of 0.2 mass% relative to the blast furnace slag as a slurry component.

[0071] Example 8 Blast furnace slag was used as the hydraulic material (binder), and the mass ratio of water to blast furnace slag (W / B) was 0.35. Blast furnace slag and water were placed in a beaker, and sodium hydroxide (NaOH) was added as an alkaline stimulant in an amount such that the mass ratio of Na2O from NaOH to the hydraulic material (binder) (Na2O / B) was 0.045, and a dispersant "MJ-3" was added in an amount of 0.2 mass% (solid content equivalent) to the blast furnace slag. The mixture was mixed by hand at room temperature (about 20°C) for 30 seconds to prepare composition slurry 8.

[0072] Example 9 Composition slurry 9 was obtained in the same manner as in Example 8, except that the mass ratio (solid content equivalent) of the dispersant "MJ-3" to the blast furnace slag was changed to 0.15 mass%, and further, a hardening inhibitor "KS-1" was added as a slurry component in a mass ratio (solid content equivalent) of 0.2 mass% to the blast furnace slag.

[0073] The component compositions of composition slurries 6 to 9 (Examples 6 to 9) are shown in Table 2 below. In Table 2, "mass % / B" indicates the mass ratio % of the corresponding component to the hydraulic material (binder) (the same applies to Table 3). [Table 2]

[0074] Composition slurries 6 to 9 (Examples 6 to 9) were subjected to the measurement tests of the above physical properties (i) to (iii). Here, in the measurement of the compressive strength of the composition slurry in (ii) above, the compressive strength was measured when the sample could be demolded after curing in a carbon dioxide atmosphere for one day (24 hours). In addition, in the measurement of the amount of fixed carbon dioxide of the composition slurry in (iii) above, the values ​​were measured after curing in a carbon dioxide atmosphere for one day (24 hours) and after curing for 14 days.

[0075] The results of measuring the physical properties (i) to (iii) of Composition Slurries 6 to 9 (Examples 6 to 9) are shown in Table 3 below. [Table 3] *1: Figure 2 shows a photograph of the appearance of composition slurry 7 (containing no alkaline irritant but a chelating agent) when it was removed from the mold after being in contact with carbon dioxide for 24 hours. From this photograph, it can be understood that it was in a state where "removal from the mold was impossible" as defined above. In other words, the adhesion of the slurry to the inner surface of the mold was partially maintained, and part of the hardened material was damaged when it was removed from the mold. *2: Figure 3(A) shows a photograph of the appearance of composition slurry 8 (containing an alkaline stimulant and not containing a hardening inhibitor) when it was removed from the mold after being in contact with carbon dioxide for 24 hours. From this photograph, it can be understood that it was in a state where it was "possible to be removed from the mold" as defined above. In other words, the adhesion of the slurry to the inner surface of the mold was not maintained, and the slurry had hardened overall. *3: Figure 3(B) shows the appearance of composition slurry 9 (containing both an alkali stimulant and a hardening inhibitor) when it was removed from the mold after being in contact with carbon dioxide for 24 hours. From this photograph, it can be understood that it was in a state where "removal from the mold is impossible" according to the above definition. In other words, the hardening of the slurry had hardly progressed within the mold. *4: The compressive strength measured after 14 days of curing in a carbon dioxide atmosphere was 7.5N / mm 2 It was.

[0076] From the results shown in Table 3, it was found that the space filling method according to the present invention can increase the amount of carbon dioxide fixed by adding an appropriate additive, even if the composition does not contain an alkaline irritant. In particular, a high amount of carbon dioxide was fixed when a chelating agent was added. The amount of carbon dioxide fixed was greater when the composition contained an alkaline irritant than when it did not contain the alkaline irritant. When the composition contains an alkaline irritant, the amount of carbon dioxide fixed increases while the hardening speed also tends to increase, but by adding a hardening inhibitor as an additive, the hardening speed can be controlled to a low level, and it was found that after 14 days of curing in a carbon dioxide atmosphere, hardening progresses and a suitable strength is reached. Thus, according to the method for filling spaces according to the present invention, regardless of the presence or absence of an alkaline irritant, a hardening speed delayed by days can be obtained, which is considered to enable reliable filling and filling of every corner of spaces with complex shapes. [Explanation of symbols]

[0077] 1: Space Buried System 2: Carbon dioxide storage facility 3: Carbon dioxide injection well 4: Carbon dioxide injection pipe 5: Underground aquifers 6: Coal seam 7: Underground coal mining site of underground coal mine 8: Space to be buried

Claims

1. A method for filling an underground space using a borehole, comprising: Preparing a composition containing a hydraulic material and at least one selected from the group consisting of an alkaline stimulant, a dispersant, and a hardening inhibitor; and injecting a slurry containing the composition into the underground space using a well and reacting the slurry with carbon dioxide to fill the underground space, the reaction being carried out by either (i) forming a mixture of the slurry and carbon dioxide prior to introducing the slurry and carbon dioxide into the underground space and then injecting the mixture into the underground space, or (ii) filling the underground space with the slurry and then introducing carbon dioxide into the underground space.

2. The method of claim 1 , wherein the underground space comprises at least one selected from the group consisting of a void in an earth formation, an underground tunnel, and a coal mine.

3. The method of claim 1 or 2, wherein the hydraulic material comprises an aluminosilicate material.

4. The method of claim 3 , wherein the aluminosilicate material comprises blast furnace slag.

5. 3. The method of claim 1 or 2, wherein the alkaline irritant comprises sodium hydroxide.

6. The method of claim 1 or 2, wherein the dispersing agent comprises a polycarboxylic acid based polymer.

7. The method according to claim 1 or 2, wherein the hardening inhibitor comprises at least one member selected from the group consisting of an oxycarboxylic acid or a salt thereof, a keto acid or a salt thereof, a sugar, and a sugar alcohol.

8. A buried system for an underground space, comprising: a slurry preparation unit that prepares a slurry using a composition containing a hydraulic material and at least one selected from the group consisting of an alkaline stimulant, a dispersant, and a hardening inhibitor; a slurry injection unit that injects the slurry or a mixture of the slurry and carbon dioxide into the underground space; When the slurry injection unit is a slurry injection unit that injects the slurry into the underground space without carbon dioxide, the system further includes a carbon dioxide injection unit that separately injects carbon dioxide into the underground space filled with the slurry.

9. A method for filling an underground space using a borehole, comprising: Preparing a composition containing an aluminosilicate material and an alkaline irritant; adding a dispersant or a set inhibitor to the composition; and and injecting a slurry containing the composition into the underground space using a well and reacting the slurry with carbon dioxide to fill the underground space, the reaction being carried out by (i) forming a mixture of the slurry and carbon dioxide prior to introducing the slurry and carbon dioxide into the underground space and then injecting the mixture into the underground space, or (ii) filling the underground space with the slurry and then introducing carbon dioxide into the underground space.

10. The method of claim 9, wherein the aluminosilicate material comprises blast furnace slag and the alkaline irritant comprises sodium hydroxide.

11. The method of claim 9 or 10, wherein the dispersant comprises a polycarboxylic acid-based polymer.

12. The method described in claim 9 or 10, wherein the hardening inhibitor comprises at least one selected from the group consisting of an oxycarboxylic acid or a salt thereof, a keto acid or a salt thereof, a sugar, and a sugar alcohol.